Autocrítica de publicaciones previas basadas en corpus: Análisis DAFO - Santamaría Urbieta, Alexandra; Alcalde Peñalver, Elena (MonTi Monografías de Traducción e Interpretación, 2021)
The objective of this article is to reflect and make self-criticism on four previous publications elaborated jointly by the authors and in which a corpus methodology was used. For this purpose, the SWOT methodology (Strengths, Weaknesses, Opportunities and Threats) will be used, which will allow us to analyze, on the one hand, the direction towards which corpus-based translation studies are heading and, on the other, what would need to be maintained, improved or modified in publications of this type. Through a first theoretical analysis, in which a tour of corpus-based studies will be conducted, we will move on to present the methodology used to analyze, from a critical point of view, the four publications of the authors. We consider that this article will have a double effect at the teaching and research levels and that it will therefore benefit Translation Studies